Analysis of the Impact of Delayed Chronic Drug Claims on Hospital Healthcare Service Quality: Systematic Literature Review - Rr. Devi Noviana Setyoningsih; Cahya Tri Purnami; Antono Suryoputro (Universitas Ibn Khaldun Bogor, 2026)
Delays in submitting reimbursement claims for chronic drug result in deferred payments, adversely affecting hospital cash flow. This financial strain leads to delays in employee compensation and challenges in ensuring adequate chronic drug availability for patients. This study aims to analyze how chronic drug claim processing delays impact the quality of healthcare services delivered by hospitals. This study utilizes a systematic literature review methodology, searching the PubMed, Scopus, and Google Scholar databases for publications from 2015-2025. The search strategy employs the following keywords: